Dual-modulation of micro-photoluminescence in rare-earth-doped crystals by femtosecond laser irradiation for 5D optical data storage. (August 2023) - Ren, Yingying; Li, Yu; Guo, Kaishun; Cui, Zemeng; Wang, Chao; Tan, Yuanxin; Liu, Hongliang; Cai, Yangjian
Highlights: Micro-structures are fabricated in Pr:YLF crystals by femtosecond laser irradiation. Dual-modulation of micro-photoluminescence is found within broad parameter windows. Optical data are encrypted in the crystal with intensity and wavelength multiplexing. Erasure energy threshold is demonstrated with secondary femtosecond laser irradiation. Spatially-selective rewriting and erasure of encrypted information are realized. Abstract: In transparent dielectric materials, the property modulation induced by femtosecond laser irradiation (FLI) holds great promise for optical storage due to the advantages of high resolution, material flexibility and 3D recording capability. However, the benefits are often mitigated by its incapability of information multiplexing or stringent requirements on fabrication conditions. Here, based on the dual-modulation of micro-photoluminescence (μ-PL) in Pr:YLF crystals by applying FLI, a novel strategy for optical data storage (ODS) is proposed and experimentally demonstrated. Multiple laser parameters within broad ranges can be used to fine-tune the μ-PL emission bands of Pr 3+ ions to create storage voxels, which makes the information recording more feasible and flexible from a perspective of practical application. Remarkably, the dual modulation of spectral features at around 638 and 641 nm, in combination with the innovative design of voxels, make it possible to realize both emission-intensity-multiplexing and emission-wavelength-multiplexing, meeting the requirements for large memory capacity and high encryption of new generation ODS. Furthermore, the spatially selective control of μ-PL signals through secondary FLI allows for rewriting and erasure of the encoded information. This work opens new opportunities for rare-earth-doped materials in the applications of multidimensional rewritable/erasable high-density optical data storage and optical information encryption.